Prispremier för honung : med fokus på ekologiskt och svenskproducerat - Möller, Annie (SLU/Dept. of Economics, 2015)
The quantity of wild pollinators is declining worldwide. Pollinators contribute with an essential ecosystem service when helping plants to reproduce. Honeybees can partly replace the loss of wild pollinators, thus making beekeeping important. As of today, the worth of the pollination is higher than the worth of the honey production and this can be seen as a market failure. Swedish consumers have been observed to prefer Swedish produced and organic food. Because of the importance of honeybees to agriculture and consumers preferences a hedonic price model is used to study the price of honey. Seven independent variables define the price function. The independent variables included in the model are as follows: production country, method of production, packaging, size of the packaging, texture, kind of honey and branding. The implicit price of a characteristic is the first order derivative of the hedonic price function with respect to the characteristic. Data has been collected in stores in Uppsala and the dataset consist of 247 observations. The results show that honey produced in Sweden has a price premium of 37 SEK and that organic honey has a price premium of 14 SEK. The results of the study gives incentives for policymakers to see the pollination as a positive external effect and give beekeepers subsidies as a way to increase beekeeping and in that way resolve the market failure.